2022
DOI: 10.1186/s12888-022-04235-0
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of a medicines optimisation tool to protect the physical health of people with severe mental illness (OPTIMISE)

Abstract: Background The life expectancy of people with severe mental illness (SMI) is shorter than those without SMI, with multimorbidity and poorer physical health contributing to health inequality. Screening tools could potentially assist the optimisation of medicines to protect the physical health of people with SMI. The aim of our research was to design and validate a medicines optimisation tool (OPTIMISE) to help clinicians to optimise physical health in people with SMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Judicious use of pharmacological interventions will also help apply brakes to unnecessary polypharmacy in consumers with multimorbidity. Medication rationalisation tools, such as OPTIMISE by Carolan et al. (2022), can help achieve this through a systematic, evidence-based assessment of the need for pharmacological treatment.…”
Section: Clinical Utility Of the Multimorbidity Framework To Psychiatrymentioning
confidence: 99%
“…Judicious use of pharmacological interventions will also help apply brakes to unnecessary polypharmacy in consumers with multimorbidity. Medication rationalisation tools, such as OPTIMISE by Carolan et al. (2022), can help achieve this through a systematic, evidence-based assessment of the need for pharmacological treatment.…”
Section: Clinical Utility Of the Multimorbidity Framework To Psychiatrymentioning
confidence: 99%
“…The specialist mental health pharmacist (SMHP) working in the inpatient mental health setting can provide leadership and support for medicines optimisation. People with SMI are less likely to have regular contact with a general medical provider and receive routine physical health screening, monitoring or interventions (Carolan et al 2022). As a result, their time as an inpatient in a mental health setting is an ideal opportunity to optimise both physical and mental health medicines use.…”
Section: Introductionmentioning
confidence: 99%
“…Screening and assessment tools can potentially help improve physical outcomes and reduce this inequality [ 17 , 18 ]. A medicines optimisation tool, OPTIMISE, was developed and validated to assist clinicians working in psychiatry to protect the overall physical health of people with SMI.…”
mentioning
confidence: 99%
“…OPTIMISE prompts the regular assessment of CV risk in adults with SMI over 40 years using a validated risk assessment tool e.g. SCORE, QRISK2, QRISK3, ensuring that at a minimum, people with SMI are screened for CVD in equal measure with the rest of the population [ 18 ]. In applying this tool in practice, the authors identified that adults under 40 years with SMI are underserved by the current guidelines.…”
mentioning
confidence: 99%